PENGARUH PENDEKATAN BERMAIN TERHDAP HASIL BELAJAR SERVIS BAWAH BOLAVOLI MINI - E, Maulana Iskandar; Supriatna, Eka; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The research problem of this research was Is there any effect on games approach to the learning outcomes of underhand serve the volleyball mini to the male students of fourth grade students of SDN 02 Bengkayang. The research purpose was to know the effect on games approach to the learning outcomes of underhand serve the volleyball mini to the male students of fourth grade students of SDN 02 Bengkayang. The research method was experimental. The population was the male students of fourth grade students of SDN 02 Bengkayang which number 24 students. The technique sample was total sampling technique. Then, the researcher held pre-test, treatment, and post-test that was underhand serve volleyball mini. The research finding showed that the average score of pre-test was 15.29 and post-test 18.42 or it increased 13%. t value (8.91) > ttable (2.069). In conclusion, there is an effect on games approach to the learning outcomes of underhand serve volleyball mini. Keywords: Games approach, the learning outcomes of underhand serve the volleyball mini. Abstrak: Permasalahan dalam penelitian ini adalah Apakah ada pengaruh pendekatan bermain terhadap hasil belajar servis bawah bolavoli mini pada siswa putra kelas IV SDN 02 Bengkayang. Tujuan Penelitian ini adalah untuk mengetahui pengaruh pendekatan bermain bolavoli terhadap hasil belajar servis bawah pada siswa putra kelas IV SDN 02 bengkayang. Metode Penelitian ini adalah eksperimen. Populasi penelitiannya adalah siswa putra kelas IV SDN 02 bengkayang yang berjumlah 24 orang. Teknik pengambilan sampel menggunakan teknik total sampling. Kemudian dilakukan tes awal, treatmen, dan tes akhir, yaitu servis bawah bolavoli. Hasil penelitian menunjukkan bahwa nilai rata-rata pre-test 15,29 dan post-test 18,42 atau mengalami peningkatan sebesar 13%. Nilai t hitung (8,91) > ttabel (2,069). Kesimpulan dalam penelitian ini adalah adanya pengaruh pendekatan bermain terhadap hasil belajar servis bawah bolavoli mini. Kata kunci : Pendekatan bermain, Hasil belajar servis bawah bolavoli mini.